Respuesta :
just substitute the values in.
if f (x)=-3x+1
a.) f (1)=-3(1)+1
solve.
-3(1)=-3+1=-2
b.) f(-2)=-3(-2)+1
-3(-2)=6+1=7
if f (x)=-3x+1
a.) f (1)=-3(1)+1
solve.
-3(1)=-3+1=-2
b.) f(-2)=-3(-2)+1
-3(-2)=6+1=7
a. f(1) = -3(1)+1
= -3+1
= -2
b. f(-2) = -3(-2)+1
= 6+1
=7
for this question you just plug in the number given for x in the place of x in the equation and then you solve it as you usually do.
= -3+1
= -2
b. f(-2) = -3(-2)+1
= 6+1
=7
for this question you just plug in the number given for x in the place of x in the equation and then you solve it as you usually do.